2020
DOI: 10.3126/nrber.v32i2.35298
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Optimum Growth-Maximizing Public Debt Threshold for Nepal

Abstract: One of the common agenda of underdeveloped economies is to achieve a high and sustainable level of economic growth in the long run. Domestic and external borrowings are playing a crucial role in fulfilling the resource gap in the context of Nepal for a long period. A growing number of recent studies support the idea of a debt threshold level (turning point) above which debt starts reducing economic growth. This paper empirically investigates the relationship between economic growth and several other factors (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 28 publications
(40 reference statements)
3
23
0
Order By: Relevance
“…This figure also illustrates that, first, the debt curve for this bivariate quadratic function (i.e., equation 4) is strictly concave or inverted U-shape curve which shows an inverse relationship of growth with debt and, second, that the resulted value (i.e., 48.42 percent of GDP) is an optimum value of debtthreshold beyond which a slight increase in debt acquisition will disrupt the whole growth process and will lead to foster adverse effects on the economy. Further, these estimates are similar to the conclusion made by Nguyen et al(2003), Mupunga and Roux (2015), Baharumshah et al (2016), Tran (2018, Khanfir (2019), Zaghdoudi (2019), and Bhatta and Mishra (2020). These results also highlight the need of special policy intervention from the central government for keeping the magnitude of debt below the debt threshold.…”
Section: Analysis Of the Relative Maxima And Minimasupporting
confidence: 88%
See 1 more Smart Citation
“…This figure also illustrates that, first, the debt curve for this bivariate quadratic function (i.e., equation 4) is strictly concave or inverted U-shape curve which shows an inverse relationship of growth with debt and, second, that the resulted value (i.e., 48.42 percent of GDP) is an optimum value of debtthreshold beyond which a slight increase in debt acquisition will disrupt the whole growth process and will lead to foster adverse effects on the economy. Further, these estimates are similar to the conclusion made by Nguyen et al(2003), Mupunga and Roux (2015), Baharumshah et al (2016), Tran (2018, Khanfir (2019), Zaghdoudi (2019), and Bhatta and Mishra (2020). These results also highlight the need of special policy intervention from the central government for keeping the magnitude of debt below the debt threshold.…”
Section: Analysis Of the Relative Maxima And Minimasupporting
confidence: 88%
“…Khanfir (2019) and Zaghoudi (2019) stressed on fiscal consolidation and dragging the debt burden below the debt threshold towards stimulating economic growth. Ndoricimpa (2020) and Bhatta and Mishra (2020) focused on accelerating the economic growth and reducing the negative impact of debt which was found drastic in debt-abundant countries as compared to debtmoderate economies. With regards to the application of this theory in Pakistan, we have come across only a few papers that have examined the theories and concepts of this inverse relationship and have concluded that this relationship exists in the form of an inverted-U shape curve.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Minhaj-ud-Din, Azam & Tariq (2020) concluded that excessive accumulation of external debt is inimical and curse for public investment and economic productivity. Bhatta and Mishra (2020) estimated that optimal debt should not exceed 33% of GDP which is mandatory for accelerating the economic growth of Nepal. Table 1 represents a brief sketch of the empirical work held on this topic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Step 5: Estimating the optimum level of debt-threshold by using the quadratic bivariate model based on the long-run coefficients of the ARDL model listed in Table 6 (Bhatta & Mishra, 2020). Mathematically:…”
Section: Estimation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation